Laser-activated selective metallization resin composition and preparation method and application thereof

By using metal oxides as laser sensitization aids on the surface of the polymer, laser activation and electroless plating are solved, and the problems of insufficient copper layer thickness and metal waste in the prior art are realized, and a metal plating with high thickness and excellent conductivity is achieved, which has wide industrial application value.

CN119752092APending Publication Date: 2025-04-04SICHUAN UNIV

Patent Information

Application Number
CN202411932686.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing laser activation selective metallization technology is difficult to form a high-thick copper layer on the surface of the polymer, resulting in poor electrical conductivity of the circuit and waste of metal copper.

Method used

Using metal oxides as laser sensitization aids, laser activation and electroless plating are performed with the polymer composition to form a high-thickness metal plating layer.

Benefits of technology

It is achieved that resin compositions with excellent coating thickness and strength are obtained at a lower metal oxide addition amount, suitable for industrial production, and the copper layer thickness can reach the minimum standards for common PCB board surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a laser-activated selective metallization resin composition, which is composed of the following components in percentage by weight: 1-45% of metal oxide and 55-99% of polymer. The thickness of a copper layer on the surface of a resin composition can exceed 13.3 micrometers under the condition that the addition amount of the metal oxide laser sensitization auxiliary agent is as low as 1%, the thickness of the copper layer is larger, and therefore the prepared copper layer has better conductivity. Moreover, the thickness of the copper layer on the surface of the resin composition provided by the invention is up to 61.2 microns, which reaches the thickness of the copper layer on the surface of a common PCB (Printed Circuit Board). Therefore, the laser sensitization auxiliary agent and the resin composition provided by the invention have better practical application value in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of laser sensitization additives, and specifically relates to a laser-activated selective metallized resin composition and a preparation method and application thereof. Background Art

[0002] Laser activated selective metallization (LISM) uses a computer to control the movement of the laser according to the trajectory of the conductive pattern, and projects the laser onto the molded three-dimensional plastic device. In a few seconds, the circuit pattern is activated, and then the activated surface is chemically plated so that metals such as copper, nickel, and gold are deposited in the activated area to form a conductive circuit. This process can not only achieve high-flexibility production, but also make ultra-fine circuit manufacturing and fine assembly possible.

[0003] Compared with traditional selective metallization methods, laser activated selective metallization technology has the advantages of high production efficiency, low cost, small product size, flexible design, the ability to prepare three-dimensional metal patterns, and high conductivity of the metal layer obtained by chemical plating. Therefore, it is widely used in communications, electronic equipment, medical equipment and other fields. If you want to change the circuit pattern, you only need to redesign the circuit pattern through a computer without the need for an additional mask.

[0004] The laser-activated selective metallization process usually uses laser to activate the surface of the polymer part first, and then uses chemical plating to deposit a metal layer in the laser-activated area to obtain the required metal circuits and patterns. However, most polymers themselves have weak absorption of lasers, and specific laser sensitization additives need to be added to the polymer matrix.

[0005] Chinese patent CN202111183962.1 discloses a tungsten-containing laser sensitization aid, which is mainly tungsten oxide, tungsten sulfide, tungsten-containing acid, and tungsten-containing salt; Chinese patent CN202111470430.6 discloses an oxide laser sensitization aid, which is mainly dysprosium oxide, thulium oxide, erbium oxide, lanthanum oxide, niobium oxide, neodymium oxide, praseodymium oxide, samarium oxide, cerium oxide, terbium oxide, yttrium oxide, europium oxide, nickel oxide, tellurium oxide, and zirconium oxide. The laser sensitization aid disclosed in this patent document is relatively expensive.

[0006] In addition, the maximum copper layer thickness on the surface of the resin composition prepared by Chinese patent CN202111183962.1 is 8.1 μm, and the maximum copper layer thickness on the surface of the resin composition prepared by Chinese patent CN202111470430.6 is 12.7 μm. The lower copper layer thickness will lead to poor circuit conductivity.

[0007] Printed circuit boards (PCBs) are usually made by subtractive manufacturing to prepare a metal copper layer on a polymer surface, which inevitably results in waste of metal copper. The thickness of the copper layer on the PCB surface can vary depending on different applications and needs, but there are several common copper layer thickness standards: 1oz (35μm): This is the most common copper layer thickness, suitable for most PCB applications, providing a good balance between conductivity and cost. 2oz (70μm): This thickness of copper layer is suitable for applications that need to carry larger currents, such as high-current switching power supplies. 3oz (105μm): Suitable for applications with higher current carrying capacity requirements, or for use in high-power density electronic products. According to the T / CPCA 6045-202X standard, the minimum thickness of the common PCB copper layer is 35μm.

[0008] As an additive manufacturing method, LISM reduces the waste of copper layer compared to the preparation process of PCB, but the thickness of the copper layer obtained is relatively low. The copper layer thickness reported so far is far from the minimum copper layer thickness on the surface of PCB board. In industry, if the copper layer thickness is to be the same as that on the surface of PCB board, subsequent copper electroplating and gold electroplating operations are usually required. Therefore, it is very necessary to propose a resin composition material that can directly obtain a high-thickness copper layer through LISM. Summary of the invention

[0009] The invention provides an application of a metal oxide in preparing a laser-activated selective metallized resin composition, a laser-activated selective metallized resin composition and a laser-activated resin product with excellent chemical plating effect.

[0010] The present invention provides a laser-activated selective metallized resin composition, which is composed of the following components in weight percentage: 1% to 45% of metal oxide and 55% to 99% of polymer;

[0011] The metal oxide is at least one of ytterbium oxide, lutetium oxide, holmium oxide, gadolinium oxide, scandium oxide, strontium oxide, gallium oxide, hafnium oxide, cobalt oxide, and tantalum oxide;

[0012] The polymer is selected from any one or more of polycarbonate, acrylonitrile-butadiene-styrene copolymer, styrene-acrylonitrile copolymer, polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyamide, polystyrene, K resin, styrene-acrylate-acrylonitrile copolymer, PEN, polyphenylene ether, polyphenylene sulfide, polyetheretherketone, polyurethane, nylon elastomer, LCP, SEBS, SEPS, SEEPS, POE, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, and polyester elastomer;

[0013] The laser activation is performed using a laser with a wavelength of 190-1064 nm.

[0014] Among them, the oxide of ytterbium is ytterbium oxide; the oxide of lutetium is lutetium oxide; the oxide of holmium is holmium oxide; the oxide of gadolinium is gadolinium oxide; the oxide of scandium is scandium oxide; the oxide of strontium is strontium oxide; the oxide of gallium is gallium oxide; the oxide of hafnium is hafnium oxide; the oxide of cobalt is cobalt oxide; and the oxide of tantalum is tantalum oxide.

[0015] Preferably, it is composed of the following components in weight percentage: 10% to 45% of metal oxide, 55% to 80% of polymer;

[0016] The metal oxide is at least one of cobalt oxide, ytterbium oxide, lutetium oxide, scandium oxide, hafnium oxide, tantalum oxide, holmium oxide, strontium oxide, gallium oxide and gadolinium oxide;

[0017] The polymer is at least one of ABS, polypropylene, SEBS, polycarbonate, polyamide 66, polyethylene, polystyrene, polybutylene terephthalate and polyethylene terephthalate.

[0018] Further preferably, it is composed of one of the following components in weight percentage:

[0019] ABS 45%, cobalt oxide 55%, laser activation wavelength: 395nm;

[0020] ABS 45%, Ytterbium oxide 55%, laser activation wavelength: 355nm;

[0021] Polypropylene 45%, lutetium oxide 55%, laser activation wavelength: 1064nm;

[0022] SEBS 45%, scandium oxide 55%, laser activation wavelength: 355nm;

[0023] Polycarbonate 45%, hafnium oxide 55%, laser activation wavelength: 190nm;

[0024] Polyamide 66 45%, tantalum oxide 55%, laser activation wavelength: 532nm;

[0025] Polyethylene 45%, holmium oxide 55%, laser activation wavelength: 532nm;

[0026] Polystyrene 45%, strontium oxide 55%, laser activation wavelength: 190nm;

[0027] Polybutylene terephthalate 45%, gallium oxide 55%, laser activation wavelength: 1064nm;

[0028] Polyamide 66 20%, tantalum oxide 80%, laser activation wavelength: 532nm;

[0029] Polyethylene terephthalate 45%, gadolinium oxide 55%, laser activation wavelength: 395nm;

[0030] ABS 20%, cobalt oxide 80%, laser activation wavelength: 395nm;

[0031] Polystyrene 10%, strontium oxide 90%, laser activation wavelength: 190nm;

[0032] Polycarbonate 20%, hafnium oxide 80%, laser activation wavelength: 190nm;

[0033] Polybutylene terephthalate 20%, gallium oxide 80%, laser activation wavelength: 1064nm;

[0034] Polypropylene 10%, lutetium oxide 90%, laser activation wavelength: 1064nm;

[0035] Polyethylene terephthalate 10%, gadolinium oxide 90%, laser activation wavelength: 395nm;

[0036] Polycarbonate 10%, hafnium oxide 90%, laser activation wavelength: 190nm;

[0037] Polybutylene terephthalate 10%, gallium oxide 90%, laser activation wavelength: 1064nm;

[0038] Polyamide 66 10%, tantalum oxide 90%, laser activation wavelength: 532nm;

[0039] ABS 10%, cobalt oxide 90%, laser activation wavelength: 395nm;

[0040] ABS 10%, Ytterbium oxide 90%, laser activation wavelength: 355nm;

[0041] SEBS 10%, scandium oxide 90%, laser activation wavelength: 355nm.

[0042] The average particle size of the metal oxide is less than or equal to 150 μm; preferably, the average particle size of the metal oxide is 0.010 μm to 50 μm; more preferably, the average particle size of the metal oxide is 0.2 μm to 10 μm.

[0043] The present invention also provides a method for preparing the resin composition, which comprises the following steps:

[0044] a. Take metal oxide and polymer, mix them evenly to obtain a mixture;

[0045] b. Melt-blending and granulating the mixture obtained in step a to obtain a laser-activated selective metallized resin composition.

[0046] The resin composition of the present invention is used for preparing high-thickness metal coating materials, and the coating thickness is greater than or equal to 35 μm.

[0047] The present invention also provides application of the resin composition in micro-processing materials, wherein the micro-processing materials include micro-circuit materials.

[0048] The present invention provides a fine circuit material, which is formed by selectively activating the resin composition under a laser with a wavelength of 190-1064nm, and then chemically plating it to deposit a conductive metal in the activated area; preferably, the conductive metal is copper, nickel or gold.

[0049] The present invention also provides a material having a high-thickness metal coating on the surface, which is formed by selectively activating the resin composition under a laser with a wavelength of 190-1064nm, and then chemically plating to deposit a conductive metal in the activated area; preferably, the conductive metal is copper, nickel or gold. The thickness of the coating is greater than or equal to 35μm.

[0050] The experimental results show that the metal oxide of the present invention has excellent effect with small addition amount. The metal oxide laser sensitization aid of the present invention has various types and can be made into different laser activated selective metallized resin compositions after being processed with polymers, which are suitable for different application scenarios.

[0051] The metal oxide laser sensitization aid provided by the present invention can have a copper layer thickness of more than 13.3 μm on the surface of the resin composition when the addition amount is as low as 1%, and the copper layer thickness is greater, so the prepared copper layer has better conductivity. In addition, the copper layer thickness on the surface of the resin composition provided by the present invention can reach up to 61.2 μm, reaching the copper layer thickness on the surface of a common PCB board. Therefore, the laser sensitization aid and the resin composition provided by the present invention have better practical application value in practical applications.

[0052] The metal oxide of the present invention exhibits excellent laser activation ability under the action of laser in the wavelength range of 190-1064nm. The prepared laser-activated selectively metallized resin has a light color and a good chemical plating effect after activation. When the addition amount is as low as 1wt%, the coating thickness of the obtained resin composition reaches more than 13μm, and a PCB copper layer of more than 35μm can also be prepared. The coating strength tested by a hundred-grid knife (ASTM D3359) reaches the highest level of 5B, and the application prospect is very broad.

[0053] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0054] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. DETAILED DESCRIPTION

[0055] The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.

[0056] (1) The equipment information used in the present invention is as follows:

[0057] Twin-screw extruder, screw diameter 35 mm, screw length-diameter ratio 36:1, produced by Nanjing Jieente Electromechanical Co., Ltd.;

[0058] Injection molding machine, model MA600, produced by Haitian Machinery Co., Ltd.;

[0059] Laser marking machine, model MUV-ER, pulse laser marking machine, maximum laser power 5W, laser wavelength 355nm;

[0060] Laser marking machine, model MV-U, pulse laser marking machine, maximum laser power 3W, laser wavelength 190nm;

[0061] Laser marking machine, model DZ-Q, pulse laser marking machine, maximum laser power 8W, laser wavelength 395nm;

[0062] Laser marking machine, model MF-EA, fiber pulse laser marking machine, maximum laser power 20W, laser wavelength 1064nm;

[0063] Laser marking machine, model YK-F20G, fiber pulse laser marking machine, laser maximum power 10W, laser wavelength 532nm.

[0064] (2) The specific information of the base polymer used to prepare the standard sample of the present invention is as follows:

[0065] Acrylonitrile butadiene styrene (ABS): Chimei, Taiwan, China, PA757 (density: 1.05 g / cm3; melt flow rate: 1.8 g / 10 min, 200°C, 5 kg).

[0066] Polycarbonate: General Electric Company, PC121R (density: 1.2 g / cm3; melt flow rate: 17.5 g / 10 min, 300°C, 1.2 Kg; heat deformation temperature: 125°C).

[0067] Polystyrene: Duzishan Petrochemical, GPPS-500 (density: 1.04 g / cm3; melt flow rate: 5 g / 10 min, 200°C, 5 Kg; heat deformation temperature: 89°C).

[0068] Polyethylene terephthalate: Yuanfang Industry, CB-602 (density: 1.40 g / cm3; melting temperature: 245°C).

[0069] Polybutylene terephthalate: BASF, Germany, PBTB4500 (density: 1.3 g / cm3; melting temperature: 230°C).

[0070] SEBS: Japan Kuraray, HYBRA7311F (density: 0.89 g / cm3; melting temperature: 200°C).

[0071] Polyamide 66: LANXESS, Germany, A30S (density: 1.14 g / cm3; melting temperature: 260°C).

[0072] Polypropylene: Daqing Petrochemical, T30S (density: 0.9g / cm3; melting temperature: 189℃)

[0073] Polyethylene (PE): Maoming Petrochemical, TR144, a high-density polyethylene (density: 0.95g / cm3; melting temperature: 142°C)

[0074] Polyurethane: Bayer, Germany, 9385 (density 1.005g / cm3, melting temperature: 170℃)

[0075] Polyester elastomer: Korea Cologne, KP3355 (density 1.06g / cm3, melting temperature: 170℃)

[0076] Example 1

[0077] First, 99 g of ABS resin and 1 g of ytterbium oxide powder (average particle size of 3 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 210°C to obtain a laser-activated selective metallized resin composition.

[0078] Then, the prepared laser activated selective metallized resin composition was injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 210°C.

[0079] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 355 nm, speed of 2000 mm / s, laser energy of 3 W, and laser frequency of 60 kHz.

[0080] According to the laser-activated selective metallized resin composition chemical plating method and process known in the art, the plastic sheet after laser activation is chemically copper-plated. The chemical copper plating adopts a reduction system with formaldehyde as a reducing agent and copper sulfate as a metallic copper salt. The resin composition is placed in a 50°C chemical copper plating solution for reaction for 30 minutes, and air is continuously introduced for stirring to ensure the uniformity of the copper layer.

[0081] After chemical copper plating, the following effects and / or performance tests are performed:

[0082] (1) Chemical plating effect: visual inspection;

[0083] (2) Thickness of electroless copper plating: tested according to ASTM B568 (2009);

[0084] (3) Grid knife test: According to ASTM D3359, use a grid cutter to draw a small square grid of 1mm×1mm in the copper-plated layer area. Then, stick Scotch 3M 600-1PK test tape to the grid area and quickly tear off the tape. The grade of adhesion strength is determined based on the area where the copper layer falls off. In the ASTM D3359 grading standard, the higher the grade, the higher the adhesion between the polymer substrate and the copper-plated layer. Among them:

[0085] The spalling area of ​​0B mesh is greater than 65%;

[0086] The peeling area of ​​1B grid is 35%-65%;

[0087] The peeling area of ​​2B mesh is 15%-35%;

[0088] The peeling area of ​​3B mesh is 5%-15%;

[0089] The spalling area of ​​4B mesh is 5%;

[0090] 5B has no mesh peeling.

[0091] The test results are shown in Table 1.

[0092] Example 2

[0093] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 1, except that the matrix polymer and the metal oxide used were: 95 g of ABS resin and 5 g of ytterbium oxide powder.

[0094] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0095] Example 3

[0096] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 1, except that the matrix polymer and the metal oxide used were: 90 g of ABS resin and 10 g of ytterbium oxide powder.

[0097] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0098] Example 4

[0099] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 1, except that the matrix polymer and the metal oxide used were: 55 g of ABS resin and 45 g of ytterbium oxide powder.

[0100] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0101] Example 5

[0102] 99 g of polypropylene resin and 1 g of lutetium oxide powder (average particle size of 2 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 190°C to obtain a laser-activated selective metallized resin composition.

[0103] The prepared laser activated selective metallized resin composition is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 190°C.

[0104] The plastic sheet was laser activated using the following conditions: pulsed near-infrared laser, laser wavelength of 1064 nm, speed of 2000 mm / s, laser energy of 14 W, and laser frequency of 60 kHz.

[0105] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0106] Example 6

[0107] The laser activated selective metallized resin composition and the laser activated plastic sheet were prepared by referring to the method of Example 5, the only difference being that the matrix polymer and the metal oxide used were: 95 g of polypropylene resin and 5 g of lutetium oxide powder.

[0108] The test method is the same as that of Example 5. The test results are shown in Table 1.

[0109] Example 7

[0110] The laser activated selective metallized resin composition and the laser activated plastic sheet were prepared by referring to the method of Example 5, the only difference being that the matrix polymer and the metal oxide used were: 90 g of polypropylene resin and 10 g of lutetium oxide powder.

[0111] The test method is the same as that of Example 5. The test results are shown in Table 1.

[0112] Example 8

[0113] The laser activated selective metallized resin composition and the laser activated plastic sheet were prepared by referring to the method of Example 5, the only difference being that the matrix polymer and the metal oxide used were: 55 g of polypropylene resin and 45 g of lutetium oxide powder.

[0114] The test method is the same as that of Example 5. The test results are shown in Table 1.

[0115] Example 9

[0116] 98 g of polyethylene resin and 2 g of holmium oxide powder (average particle size of 5 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 160°C to obtain a laser-activated selective metallized resin composition.

[0117] The prepared laser activated selective metallized resin composition is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 160°C.

[0118] The plastic sheet was laser activated using the following conditions: green laser, laser wavelength of 532 nm, speed of 2000 mm / s, laser energy of 5 W, and laser frequency of 60 kHz.

[0119] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0120] Example 10

[0121] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 9, the only difference being that the matrix polymer and the metal oxide used were: 95 g of polyethylene resin and 5 g of holmium oxide powder.

[0122] The test method is the same as that of Example 9. The test results are shown in Table 1.

[0123] Embodiment 11

[0124] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 9, the only difference being that the matrix polymer and the metal oxide used were: 55 g of polyethylene resin and 45 g of holmium oxide powder.

[0125] The test method is the same as that of Example 8. The test results are shown in Table 1.

[0126] Example 12

[0127] 98 g of polyethylene terephthalate resin and 2 g of gadolinium oxide powder (average particle size of 8 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 240° C. to obtain a laser-activated selective metallized resin composition.

[0128] The prepared laser activated selective metallized resin composition is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 235°C.

[0129] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 395 nm, speed of 2000 mm / s, laser energy of 4 W, and laser frequency of 60 kHz.

[0130] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0131] Example 13

[0132] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 12, except that the matrix polymer and the metal oxide used were: 90 g of polyethylene terephthalate resin and 10 g of gadolinium oxide powder.

[0133] The test method is the same as that of Example 12. The test results are shown in Table 1.

[0134] Embodiment 14

[0135] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 12, except that the matrix polymer and the metal oxide used were: 55 g of polyethylene terephthalate resin and 45 g of gadolinium oxide powder.

[0136] The test method is the same as that of Example 12. The test results are shown in Table 1.

[0137] Embodiment 15

[0138] 95 g of SEBS resin and 5 g of scandium oxide powder (average particle size of 1 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed materials were placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 200°C to obtain a laser-activated selective metallized resin composition.

[0139] The prepared laser activated selective metallized resin composition is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 200°C.

[0140] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 355 nm, speed of 2000 mm / s, laser energy of 2.5 W, and laser frequency of 60 kHz.

[0141] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0142] Example 16

[0143] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 15, except that the matrix polymer and the metal oxide used were: 90 g of SEBS resin and 10 g of scandium oxide powder.

[0144] The test method is the same as that of Example 15. The test results are shown in Table 1.

[0145] Embodiment 17

[0146] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 15, the only difference being that the matrix polymer and the metal oxide used were: 55 g of SEBS resin and 45 g of scandium oxide powder.

[0147] The test method is the same as that of Example 15. The test results are shown in Table 1.

[0148] Embodiment 18

[0149] 95 g of polystyrene resin and 5 g of strontium oxide powder (average particle size of 1 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 200°C to obtain a laser-activated selective metallized resin composition.

[0150] The prepared laser activated selective metallized resin composition is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 205°C.

[0151] The plastic sheet was laser activated using the following conditions: pulsed laser, laser wavelength of 190 nm, speed of 2000 mm / s, laser energy of 2 W, and laser frequency of 60 kHz.

[0152] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0153] Embodiment 19

[0154] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 18, the only difference being that the matrix polymer and the metal oxide used were: 90 g of polystyrene resin and 10 g of strontium oxide powder.

[0155] The test method is the same as that of Example 18, and the test results are shown in Table 1.

[0156] Embodiment 20

[0157] The laser-activated selective metallized resin composition and the laser-activated plastic sheet were prepared by referring to the method of Example 18, the only difference being that the matrix polymer and the metal oxide used were: 55 g of polystyrene resin and 45 g of strontium oxide powder.

[0158] The test method is the same as that of Example 18, and the test results are shown in Table 1.

[0159] Embodiment 21

[0160] 90 g of polybutylene terephthalate resin and 10 g of gallium oxide powder (average particle size of 5 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 245° C. to obtain a laser-activated selective metallized resin composition.

[0161] The prepared laser activated selective metallized resin composition is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 240°C.

[0162] The plastic sheet was laser activated using the following conditions: pulsed near-infrared laser, laser wavelength of 1064 nm, speed of 2000 mm / s, laser energy of 12 W, and laser frequency of 60 kHz.

[0163] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0164] Embodiment 22

[0165] A laser-activated selective metallized resin composition and a laser-activated plastic sheet were prepared by referring to the method of Example 21, the only difference being that the matrix polymer and the metal oxide used were: 80 g of polybutylene terephthalate resin and 20 g of gallium oxide powder.

[0166] The test method is the same as that of Example 21, and the test results are shown in Table 1.

[0167] Embodiment 23

[0168] A laser-activated selective metallized resin composition and a laser-activated plastic sheet were prepared by referring to the method of Example 21, the only difference being that the matrix polymer and the metal oxide used were: 55 g of polybutylene terephthalate resin and 45 g of gallium oxide powder.

[0169] The test method is the same as that of Example 21, and the test results are shown in Table 1.

[0170] Embodiment 24

[0171] 90 g of polycarbonate resin and 10 g of hafnium oxide powder (average particle size of 1 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 265°C to obtain a laser-activated selective metallized resin composition.

[0172] The prepared laser activated selective metallized resin composition is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 260°C.

[0173] The plastic sheet was laser activated using the following conditions: pulsed laser, laser wavelength of 190 nm, speed of 2000 mm / s, laser energy of 1.5 W, and laser frequency of 60 kHz.

[0174] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0175] Embodiment 25

[0176] A laser activated selective metallized resin composition and a laser activated plastic sheet were prepared by referring to the method of Example 24, the only difference being that the matrix polymer and the metal oxide used were: 80 g of polycarbonate resin and 20 g of hafnium oxide powder.

[0177] The test method is the same as that of Example 24, and the test results are shown in Table 1.

[0178] Embodiment 26

[0179] A laser activated selective metallized resin composition and a laser activated plastic sheet were prepared by referring to the method of Example 24, the only difference being that the base polymer and the metal oxide used were: 55 g of polycarbonate resin and 45 g of hafnium oxide powder.

[0180] The test method is the same as that of Example 24, and the test results are shown in Table 1.

[0181] Embodiment 27

[0182] 90 g of ABS resin and 10 g of cobalt oxide powder (average particle size of 5 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 215°C to obtain a laser-activated selective metallized resin composition.

[0183] The prepared laser activated selective metallized resin composition was injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 210°C.

[0184] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 395 nm, speed of 2000 mm / s, laser energy of 6 W, and laser frequency of 60 kHz.

[0185] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0186] Embodiment 28

[0187] A laser-activated selective metallized resin composition and a laser-activated plastic sheet were prepared by referring to the method of Example 27, the only difference being that the matrix polymer and the metal oxide used were: 80 g of ABS resin and 20 g of cobalt oxide powder.

[0188] The test method is the same as that of Example 27. The test results are shown in Table 1.

[0189] Embodiment 29

[0190] A laser-activated selective metallized resin composition and a laser-activated plastic sheet were prepared by referring to the method of Example 27, the only difference being that the base polymer and the metal oxide used were: 55 g of ABS resin and 45 g of cobalt oxide powder.

[0191] The test method is the same as that of Example 27. The test results are shown in Table 1.

[0192] Embodiment 30

[0193] 90 g of polyamide 66 resin and 10 g of tantalum oxide powder (average particle size of 2 μm) were fully mixed in a high-speed mixer for 3 minutes; then, the mixed material was placed in a twin-screw extruder for melt extrusion and granulation at an extrusion temperature of 265°C to obtain a laser-activated selective metallized resin composition.

[0194] The prepared laser activated selective metallized resin composition was injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 265°C.

[0195] The plastic sheet was laser activated using the following conditions: green laser, laser wavelength of 532 nm, speed of 2000 mm / s, laser energy of 6 W, and laser frequency of 60 kHz.

[0196] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0197] Embodiment 31

[0198] A laser activated selective metallized resin composition and a laser activated plastic sheet were prepared by referring to the method of Example 30, the only difference being that the matrix polymer and the metal oxide used were: 80 g of polyamide 66 resin and 20 g of tantalum oxide powder.

[0199] The test method is the same as that of Example 30. The test results are shown in Table 1.

[0200] Embodiment 32

[0201] A laser-activated selective metallized resin composition and a laser-activated plastic sheet were prepared by referring to the method of Example 30, with the only difference being that the matrix polymer and the metal oxide used were: 55 g of polyamide 66 resin and 45 g of tantalum oxide powder.

[0202] The test method is the same as that of Example 30. The test results are shown in Table 1.

[0203] The test method is the same as that of Example 33, and the test results are shown in Table 1.

[0204] Comparative Example 1

[0205] The laser activated selective metallized resin composition and plastic sheet were prepared by referring to the method of Example 1, except that the matrix polymer and metal oxide used were: 99.8 g of ABS resin and 0.2 g of ytterbium oxide powder.

[0206] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 355 nm, speed of 2000 mm / s, laser energy of 3 W, and laser frequency of 60 kHz.

[0207] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0208] Comparative Example 2

[0209] The laser activated selective metallized resin composition and plastic sheet were prepared by referring to the method of Example 1, except that the base polymer and metal oxide used were: 99.6 g of polypropylene resin and 0.4 g of lutetium oxide powder.

[0210] The plastic sheet was laser activated using the following conditions: pulsed near-infrared laser, laser wavelength of 1064 nm, speed of 2000 mm / s, laser energy of 14 W, and laser frequency of 60 kHz.

[0211] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0212] Comparative Example 3

[0213] The laser activated selective metallized resin composition and plastic sheet were prepared by referring to the method of Example 1, except that the matrix polymer and metal oxide used were: 99.4 g of polyethylene resin and 0.6 g of holmium oxide powder.

[0214] The plastic sheet was laser activated using a green laser with a wavelength of 532 nm, a speed of 2000 mm / s, a laser energy of 5 W, and a laser frequency of 60 kHz.

[0215] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0216] Comparative Example 4

[0217] The plastic sheet was prepared by referring to the method of Example 1, except that the base polymer and the metal oxide used were: 99.2 g of SEBS resin and 0.8 g of holmium oxide powder.

[0218] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 355 nm, speed of 2000 mm / s, laser energy of 3 W, and laser frequency of 60 kHz.

[0219] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0220] Comparative Example 5

[0221] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was: 100 g of ABS resin.

[0222] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 355 nm, speed of 2000 mm / s, laser energy of 3 W, and laser frequency of 60 kHz.

[0223] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0224] Comparative Example 6

[0225] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was: 100 g of polypropylene resin.

[0226] The plastic sheet was laser activated using the following conditions: pulsed near-infrared laser, laser wavelength of 1064 nm, speed of 2000 mm / s, laser energy of 14 W, and laser frequency of 60 kHz.

[0227] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0228] Comparative Example 7

[0229] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was: 100 g of polyethylene resin.

[0230] The plastic sheet was laser activated using the following conditions: green laser, laser wavelength of 532 nm, speed of 2000 mm / s, laser energy of 5 W, and laser frequency of 60 kHz.

[0231] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0232] Comparative Example 8

[0233] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the matrix polymer used was 100 g of polyethylene terephthalate resin.

[0234] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 395 nm, speed of 2000 mm / s, laser energy of 4 W, and laser frequency of 60 kHz.

[0235] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0236] Comparative Example 9

[0237] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was: 100 g of SEBS resin.

[0238] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 355 nm, speed of 2000 mm / s, laser energy of 2.5 W, and laser frequency of 60 kHz.

[0239] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0240] Comparative Example 10

[0241] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the matrix polymer used was: 100 g of polystyrene resin.

[0242] The plastic sheet was laser activated using the following conditions: pulsed laser, laser wavelength of 190 nm, speed of 2000 mm / s, laser energy of 2 W, and laser frequency of 60 kHz.

[0243] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0244] Comparative Example 11

[0245] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was 100 g of polybutylene terephthalate resin.

[0246] The plastic sheet was laser activated using the following conditions: pulsed near-infrared laser, laser wavelength of 1064 nm, speed of 2000 mm / s, laser energy of 12 W, and laser frequency of 60 kHz.

[0247] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0248] Comparative Example 12

[0249] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was: 100 g of polycarbonate resin.

[0250] The plastic sheet was laser activated using the following conditions: pulsed laser, laser wavelength of 190 nm, speed of 2000 mm / s, laser energy of 1.5 W, and laser frequency of 60 kHz.

[0251] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0252] Comparative Example 13

[0253] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was 100 g of polyamide 66 resin.

[0254] The plastic sheet was laser activated using the following conditions: green laser, laser wavelength of 532 nm, speed of 2000 mm / s, laser energy of 6 W, and laser frequency of 60 kHz.

[0255] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0256] Comparative Example 14

[0257] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was: 100 g of polyurethane resin.

[0258] The plastic sheet was laser activated using the following conditions: pulsed near-infrared laser, laser wavelength of 1064 nm, speed of 2000 mm / s, laser energy of 12 W, and laser frequency of 60 kHz.

[0259] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0260] Comparative Example 15

[0261] The plastic sheet was prepared by referring to the method of Example 1, except that no metal oxide was added and the base polymer used was: 100 g of polyester elastomer resin.

[0262] The plastic sheet was laser activated using the following conditions: pulsed ultraviolet laser, laser wavelength of 355 nm, speed of 2000 mm / s, laser energy of 2.5 W, and laser frequency of 60 kHz.

[0263] The effect and / or performance test method is the same as that in Example 1, and the test results are shown in Table 1.

[0264] Table 1. Important parameters and test results of Examples 1 to 32 and Comparative Examples 1 to 15

[0265]

[0266]

[0267]

[0268] The results show that the activation effect of the resin composition with metal oxide as the laser sensitization aid is good when laser is activated with a wavelength in the range of 190-1064nm, and a chemical metal layer can be well plated on its surface.

[0269] When the metal oxide addition amount of the present invention is as low as 1wt%, the coating thickness of the obtained resin composition reaches more than 13.3μm, and the coating strength tested by a grating knife (ASTM D3359) reaches a maximum level of 5B, which is very suitable for industrial production and application. In addition, the copper layer thickness obtained by LISM on the surface of the resin composition provided by the present invention can reach up to 61.2μm, which is far greater than the copper layer thickness on the surface of a common PCB board. Therefore, the metal oxide and resin composition of the present invention have broad application prospects.

[0270] In summary, the present invention provides an application of a metal oxide in the preparation of a laser-activated selective metallized resin composition, as well as a laser-activated selective metallized resin composition and a laser-activated resin product with excellent chemical plating effect. The inventors of the present invention unexpectedly discovered that after using the metal oxide and a laser-activated resin composition with a wavelength of 190-1064nm, chemical copper plating can be well performed on its surface. On the one hand, 190-1064nm covers almost all laser wavelengths, and the activated resin composition under different laser wavelengths can give play to the advantages of the laser wavelength itself; on the other hand, the metal oxides are of various types and colors, and can be processed with polymers to make laser-activated selective metallized resin compositions with different background colors, which are suitable for different application scenarios. The present invention can obtain a resin composition with excellent coating thickness and coating strength under the condition of a relatively low amount of metal oxide added, and has excellent industrial application value.

Claims

1. A laser activated selective metallized resin composition, characterized in that: It is composed of the following components in weight percentage: 1% to 45% of metal oxide and 55% to 99% of polymer; The metal oxide is at least one of ytterbium oxide, lutetium oxide, holmium oxide, gadolinium oxide, scandium oxide, strontium oxide, gallium oxide, hafnium oxide, cobalt oxide, and tantalum oxide; The polymer is selected from any one or more of polycarbonate, acrylonitrile-butadiene-styrene copolymer, styrene-acrylonitrile copolymer, polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyamide, polystyrene, K resin, styrene-acrylate-acrylonitrile copolymer, PEN, polyphenylene ether, polyphenylene sulfide, polyetheretherketone, polyurethane, nylon elastomer, LCP, SEBS, SEPS, SEEPS, POE, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, and polyester elastomer; The laser activation is performed using a laser with a wavelength of 190-1064 nm.

2. The laser activated selective metallized resin composition according to claim 1, characterized in that: The oxide of ytterbium is ytterbium oxide; the oxide of lutetium is lutetium oxide; the oxide of holmium is holmium oxide; the oxide of gadolinium is gadolinium oxide; the oxide of scandium is scandium oxide; the oxide of strontium is strontium oxide; the oxide of gallium is gallium oxide; the oxide of hafnium is hafnium oxide; the oxide of cobalt is cobalt oxide; and the oxide of tantalum is tantalum oxide.

3. The laser activated selective metallized resin composition according to claim 2, characterized in that: It is composed of the following components in weight percentage: 10% to 45% of metal oxide and 55% to 80% of polymer; The metal oxide is at least one of cobalt oxide, ytterbium oxide, lutetium oxide, scandium oxide, hafnium oxide, tantalum oxide, holmium oxide, strontium oxide, gallium oxide and gadolinium oxide; The polymer is at least one of ABS, polypropylene, SEBS, polycarbonate, polyamide 66, polyethylene, polystyrene, polybutylene terephthalate and polyethylene terephthalate.

4. The laser activated selective metallized resin composition according to claim 3, characterized in that: It is composed of one of the following components in weight percentage: ABS 45%, cobalt oxide 55%, laser activation wavelength: 395nm; ABS 45%, Ytterbium oxide 55%, laser activation wavelength: 355nm; Polypropylene 45%, lutetium oxide 55%, laser activation wavelength: 1064nm; SEBS 45%, scandium oxide 55%, laser activation wavelength: 355nm; Polycarbonate 45%, hafnium oxide 55%, laser activation wavelength: 190nm; Polyamide 66 45%, tantalum oxide 55%, laser activation wavelength: 532nm; Polyethylene 45%, holmium oxide 55%, laser activation wavelength: 532nm; Polystyrene 45%, strontium oxide 55%, laser activation wavelength: 190nm; Polybutylene terephthalate 45%, gallium oxide 55%, laser activation wavelength: 1064nm; Polyamide 66 20%, tantalum oxide 80%, laser activation wavelength: 532nm; Polyethylene terephthalate 45%, gadolinium oxide 55%, laser activation wavelength: 395nm; ABS 20%, cobalt oxide 80%, laser activation wavelength: 395nm; Polystyrene 10%, strontium oxide 90%, laser activation wavelength: 190nm; Polycarbonate 20%, hafnium oxide 80%, laser activation wavelength: 190nm; Polybutylene terephthalate 20%, gallium oxide 80%, laser activation wavelength: 1064nm; Polypropylene 10%, lutetium oxide 90%, laser activation wavelength: 1064nm; Polyethylene terephthalate 10%, gadolinium oxide 90%, laser activation wavelength: 395nm; Polycarbonate 10%, hafnium oxide 90%, laser activation wavelength: 190nm; Polybutylene terephthalate 10%, gallium oxide 90%, laser activation wavelength: 1064nm; Polyamide 66 10%, tantalum oxide 90%, laser activation wavelength: 532nm; ABS 10%, cobalt oxide 90%, laser activation wavelength: 395nm; ABS 10%, Ytterbium oxide 90%, laser activation wavelength: 355nm; SEBS 10%, scandium oxide 90%, laser activation wavelength: 355nm.

5. The resin composition according to any one of claims 1 to 4, characterized in that: The average particle size of the metal oxide is less than or equal to 150 μm; preferably, the average particle size of the metal oxide is 0.010 μm to 50 μm; more preferably, the average particle size of the metal oxide is 0.2 μm to 10 μm.

6. The method for preparing the resin composition according to any one of claims 1 to 6, characterized in that: It includes the following steps: a. Take metal oxide and polymer, mix them evenly to obtain a mixture; b. Melt-blending and granulating the mixture obtained in step a to obtain a laser-activated selective metallized resin composition.

7. Use of the resin composition according to any one of claims 3 to 5 for preparing a high-thickness metal coating material, wherein the coating thickness is greater than or equal to 35 μm.

8. Use of the resin composition according to any one of claims 1 to 5 in a micro-processing material, wherein the micro-processing material comprises a micro-circuit material.

9. A microcircuit material, characterized in that: It is formed by selectively activating the resin composition described in any one of claims 1 to 5 under a laser with a wavelength of 190-1064nm, and then performing chemical plating to deposit a conductive metal in the activated area; preferably, the conductive metal is copper, nickel or gold.

10. A material having a high-thickness metal coating on its surface, characterized in that: It is formed by selectively activating the resin composition described in any one of claims 3 to 5 under a laser with a wavelength of 190-1064nm, and then performing chemical plating to deposit a conductive metal in the activated area; preferably, the conductive metal is copper, nickel or gold; and the thickness of the plating layer is greater than or equal to 35μm.

Citation Information

Patent Citations

  • Application of tungsten-containing sensitizing aid in preparation of laser-activatable selective metallized resin composition

    CN113831589A

  • Polytetrafluoroethylene wave-transmitting material capable of directly achieving surface metallization, preparation method and application thereof

    CN111497097A

  • Flexible liquid metal pattern based on laser activation selective metallization and preparation method thereof

    CN113727531A

  • Application of oxide in preparation of laser-activated selective metallized resin composition

    CN113956605A

  • Plating bath and method for depositing a metal layer on a substrate

    TW591124B

Cited By

  • High and low temperature resistant, acid and alkali resistant and radiation resistant wave-transparent polyphenylene sulfide composite material and preparation method thereof

    CN120484506A